RESEARCH ON RADIAL FAILURE CRITERION AND LIMIT SPEED FOR CIRCLIPS - WANG ShengBin; WANG ChunXian; WU Zhe; YE JunHui; LI HaiJiu (Jixie qiangdu)
Circlip is an important fastener, its service performance at high speed directly affects the reliability of mechanical equipment. By analyzing the centrifugal force distribution of unequal diameter circlips, simulating and testing the initial contact between circlip and shaft, the results show that the maximum centrifugal force occurs in the thickest position of the circlip, the contact state can be simplified to be three point contact, then proposing the detaching point assumption and the radial failure criterion. By using German Seeger circlip models, simulating the circlip radial displacement in high speed,according to the German circlip standard DIN471, the results show that the relative error between circlip limit speed and the DIN471 standard is less than 8% based on the detaching point assumption, which verifies the validity of the radial failure criterion. This paper has reference significance for the development of the new national circlip standard GB/T 894-2017.